Astroglia in sepsis associated encephalopathy - Shulyatnikova, T. V.; Verkhratsky, A.; Шулятнікова, Тетяна Володимирівна (Springer Science, Business Media, 2020)
Cellular pathophysiology of sepsis associated encephalopathy (SAE) remains poorly characterised. Brain pathology in SAE, which is manifested by impaired perception, consciousness and cognition, results from multifactorial events, including high levels of systemic cytokines, microbial components and endotoxins, which all damage the brain barriers, instigate neuroinflammation and cause homeostatic failure. Astrocytes, being the principal homeostatic cells of the central nervous system contribute to the brain defence against infection. Forming multifunctional anatomical barriers, astroglial cells maintain brain-systemic interfaces and restrict the damage to the nervous tissue. Astrocytes detect, produce and integrate inflammatory signals between immune cells and cells of brain parenchyma, thus regulating brain immune response. In SAE astrocytes are present in both reactive and astrogliopathic states; balance between these states define evolution of pathology and neurological outcomes. In humans pathophysiology of SAE is complicated by frequent presence of comorbidities, as well as age-related remodelling of the brain tissue with senescence of astroglia; these confounding factors further impact upon SAE progression and neurological deficits.
Keywords: Astroglia; Sepsis associated encephalopathy; Infection; Sepsis signalling; Blood brain barrier; Astrocyte reactivity; Asrtogliopathy